The concept of I Ching in Choong Kam Kow’s artwork / Sahar Amir Khansari - Sahar Amir , Khansari (2017)
Choong Kam Kow is one of the senior prominent contemporary artists in Malaysia. He obtained his Bachelor degree in Fine Arts from The National Taiwan University in 1961 and his Master of Fine Arts from The Pratt Institute, New York in 1968. He received the Honorary of Doctorate of Arts from The Robert Gordon University in Scotland due to his achievement and contribution in fine arts. What is interesting in the historical context of the Malaysian arts is the fact that Choong Kam Kow seems to be the only artist who incorporated Chinese symbols in his artworks. This research demonstrates that his use of Chinese symbols serves to convey the unity of macrocosm and microcosm in his selected artworks as well as moral values of Chinese philosophy. In addition, the artworks selected have not been previously analysed, so the researcher has selected these artworks to identify their symbols and interpret them to reveal possible meanings in order to get a deeper understanding of his art. Thus, this research is beneficial for Malaysian art due to limited studies about Choong Kam Kow’s artworks and contemporary Malaysian abstract artists. This research is also useful to the local or international art students, historians and experts who have an interest in Choong Kam Kow’s thoughts and attempt for Malaysian art progress. This research interprets ten artworks of Choong Kam Kow using Panofsky’s theory of Iconology. This approach has not been employed in previous studies and will, therefore, give us a novel explanation of the concept of the artworks and intent of the artist in relating moral values through a combination of Chinese symbols and western approaches to colour.